mTOR: A Link from the Extracellular Milieu to Transcriptional Regulation of Oligodendrocyte Development - Teresa L. Wood; Kathryn K. Bercury; Stacey E. Cifelli; Lauren E. Mursch; Jungsoo Min; Jinxiang Dai; Wendy B. Macklin (ASN Neuro, 2013)
Oligodendrocyte development is controlled by numerous extracellular signals that regulate a series of transcription factors that promote the differentiation of oligodendrocyte progenitor cells to myelinating cells in the central nervous system. A major element of this regulatory system that has only recently been studied is the intracellular signalling from surface receptors to transcription factors to down-regulate inhibitors and up-regulate inducers of oligodendrocyte differentiation and myelination. The current review focuses on one such pathway: the mTOR (mammalian target of rapamycin) pathway, which integrates signals in many cell systems and induces cell responses including cell proliferation and cell differentiation. This review describes the known functions of mTOR as they relate to oligodendrocyte development, and its recently discovered impact on oligodendrocyte differentiation and myelination. A potential model for its role in oligodendrocyte development is proposed.